A correlational study on moral distress and death attitude among oncology nurses in China - Xin, SiYing; Liang, GuanMian; Miao, QunFang; Shao, YuTong; Li, JingYi (Frontiers in Psychology, 2025)
BackgroundOncology nurses frequently care for terminally ill patients, which can expose them to moral stress and lead to moral distress. This dynamic negatively impacts their mental health and the quality of patient care. In Chinese society, where traditional cultural values often lead to an avoidance of the topic of death, nurses' attitudes toward death can be uniquely shaped, potentially affecting their ability to deliver effective end-of-life care. This study aimed to explore the prevalence of moral distress among Chinese oncology nurses and examine its relationship with attitudes toward death within this cultural context.AimTo explore factors that influence moral distress among oncology nurses and their relationship with attitudes toward death.MethodsA cross-sectional study was conducted with oncology nurses (n = 264) from two hospitals in Zhejiang Province from February 2025 to April 2025, with participants selected by purposive sampling. Data were collected using a general demographic questionnaire, the moral distress scale (MDS), and the death attitude description scale (DAP-R).ResultsThe median MDS score was 72.00 (IQR: 48.25, 105.00), while the DAP-R yielded a median score of 97.00 (IQR: 89.00, 105.00). Significant negative correlations were found between individual responsibility, harm to the patient's interests, fear of death, death avoidance, approach acceptance, and escape acceptance (P < 0.05). Besides, failure to maintain the patient's maximum interests, value conflict, and death attitudes were significantly negatively correlated (P < 0.05). Regression analysis indicated that age, fear of death, and death avoidance were key factors influencing moral distress (P < 0.05).ConclusionOur findings indicate that Chinese oncology nurses exhibit a moderate-to-high level of positive attitude toward death and a low level of moral distress. Besides, a negative correlation exists between moral distress and death attitudes. These findings suggest that Chinese cultural perspectives significantly influence nurses' attitudes toward death, which, in turn, shapes their moral decision-making and clinical practice. Nursing managers should consider implementing life-and-death education training to help nurses better understand death, strengthen their professional identity, and alleviate moral distress.